DIVERSITY AND DISTRIBUTION OF HERPETOFAUNA IN INSTITUT TEKNOLOGI SUMATERA CAMPUS AREA - Tohir, Rizki Kurnia; Siregar, Diyanti Isnani (Media Konservasi, 2021)
Land use change of rubber plantation into ITERA campus area has led to changes in the ecology of the area. Amphibians and reptiles, referred as Herpetofauna, are categorized as wild animals that are sensitive to environmental changes and are considered as bio-indicators. Wild conservation activities including herpetofauna is an essential part to the forest campus concept in ITERA. The objective of the study is to analyze the diversity and distribution of herpetofauna. This applied Visual Encounter Survey (VES) with Time Constraint Method and Glue Trap technique. This research was carried out on six observation path and 180 traps. The ecological index analysis consisted of species diversity, evenness, richness, abundance, and community similarity. Twenty-two herpetofauna species were found, including nine amphibians (5 families) and 13 reptiles (9 families). There was one reptile species with vulnerable conservation status and 3 reptile species included in CITES appendix II. The diversity index value (H ’) was 2.29; species evenness (E) value was 0.74; and species richness value was 3.33. Amphibian species with the highest abundance was Fejervarya cancrivora 1.78 individual/hour of observer, while from the reptile species was Hemidactylus frenatus 0.35 individual/hour of observer. There were 550 herpetofauna encounters, where 8 species could be found on all transects and 6 species could only be found on one transect. This research showed that the condition of ITERA habitat currently supported herpetofauna’s life and needed conservation activities to maintain herpetofauna diversity. Key words: distribution, diversity, herpetofauna, ITERA